The Impacts of Independent Directors on Firm Performance in Chinese A-share Listed Companies - Zhou, Lin-Yao (2019)
Independent directors that play an important role in firm performance has been the focus of corporate governance. This paper aims to investigate the impacts of independent directors on firm performance for Chinese A-share listed companies. The sample in this paper consists of 3720 A-share companies, excluding financial companies and Special Treatment companies listed on domestic stock exchange in China from 2013 to 2018. Multiple regression method and interview are used in this paper. The mix method is to figure out the relationship between independent directors (as dependent variables which are measure by the proportion of independent directors and the average tenure) and firm performance as dependent variables including Tobin’s Q, ROE and ratio of sales to assets. The board size, CEO duality, leverage, the proportion of SOE shares, firm size, State-control factor, industry factors and year factors are controlled. In consistent with previous studies, the results show that the impacts of independent directors on firm performance are various. The proportion of independent directors has positive relationship with Tobin’s Q in market value aspect, while it has negative relationships with ROE and ratio of sales to assets in accounting value aspect. The average tenure of independent directors has negative relationship with firm performance in all models. Overall, the finding supports that board independence should be considered carefully for different firms to improve firm performance.